2020
DOI: 10.1002/hon.2768
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of immunohistochemical expression of CD47 and SIRPα in adult T‐cell leukemia/lymphoma

Abstract: The interaction of CD47 and signal-regulatory protein alpha (SIRPα) induces "don't eat me signal", leading suppression of phagocytosis. This signal can affect the clinical course of malignant disease. Although CD47 and SIRPα expression are associated with clinicopathological features in several neoplasms, the investigation for adult T-cell leukemia/lymphoma (ATLL) has not been well-documented. This study aimed to declare the association between CD47 and SIRPα expression and clinicopathological features in ATLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Previous studies have reported that SIRPα + macrophage infiltrates were correlated with shorter overall survival and progression-free survival in other malignancies, such as diffuse large B-cell lymphoma 32 and melanoma and renal cell carcinoma 39 . However, other reports have also shown a positive correlation between SIRPα expression and good prognosis 33 . In our immunohistochemical studies, it was suggested that SIRPα enabled tumor cells to evade phagocytosis, leading to promoted tumor growth and progression, similar to PD-L1 expression in GCTB patients.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have reported that SIRPα + macrophage infiltrates were correlated with shorter overall survival and progression-free survival in other malignancies, such as diffuse large B-cell lymphoma 32 and melanoma and renal cell carcinoma 39 . However, other reports have also shown a positive correlation between SIRPα expression and good prognosis 33 . In our immunohistochemical studies, it was suggested that SIRPα enabled tumor cells to evade phagocytosis, leading to promoted tumor growth and progression, similar to PD-L1 expression in GCTB patients.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, SIRPα + , CD8 + , and FOXP3 + cells were counted per high power field in five dependent fields for each case. This process was based on previous studies, with modifications 32 , 33 , 49 51 . Statistically, the median numbers of SIRPα + , CD8 + , and FOXP3 + cells were determined as the cut-off points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTCL-NOS and ATLL cases were included in our previous studies. [16][17][18][19][20][21] All cases were reviewed by experienced hematopathologists (O. K., M. H.) according to the World Health Organization classification. 22 Clinical information was collected by reviewing the patients' medical charts.…”
Section: Patientsmentioning
confidence: 99%
“… 33 On the other hand, stromal expression of SIRPα was detected as a good prognostic factor. 38 Although the precise mechanism remains unclear, those with SIRPα-expressing stromal cells had significantly higher expression of MHC class I and/or MHC class II, and also had PD-L1 expressing stromal cells, suggesting that SIRPα-expressing stromal cells are associated with activated anti-tumor immunity. 38 …”
Section: Introductionmentioning
confidence: 98%